Hubungan Kausal antara 14 Faktor Preferensi Generasi Y dan Z dalam Memilih Jenis Hunian - Angel Tang; Hanson Endra Kusuma; Annisa Safira Riska (Universitas Sebelas Maret Surakarta, 2022)
Housing is a basic human need besides food and clothing. Housing needs are important, especially among generations Y and Z, who are currently dominating the world's population today. In determining the desired for housing, a person always relates to the criteria they want as well as these two generations. The purpose of this study is to identify the factors that influence the type of housing desired by generations Y and Z. This research uses qualitative and quantitative methods. Data collection was carried out using online questionnaires and distribution with non-random sampling method. The qualitative data were analysed using the open-coding method. Quantitative data were analysed using principal component analysis (PCA), factor analysis and multivariate regression analysis. Based on the results of the research, the factor of choosing a house is divided into fourteen factors (latent variables), namely facility and infrastructure, clean environment, natural environment, security, accessibility, landed housing attributes, vertical housing attributes, social relations, countryside or sub-urban locations, crowded environments, supporting facilities, future investment, city views, and en suite bathroom and exterior. The main factors for generations Y and Z choosing landed housing outside the city are the factors of countryside location and future investment. The main factors for generations Y and Z choosing vertical housing in the city center were accessibility, crowded surroundings, and views of the city. The main factors generation Y and Z choose cohousing in the suburbs are social relationships, sub-urban location, and en suite bathroom and exterior. Meanwhile, the factors that generation Y and Z do not want in choosing cohousing housing are the crowded environment and landed housing attributes.